2017
DOI: 10.3171/2016.7.peds16125
|View full text |Cite
|
Sign up to set email alerts
|

Posterior-only surgical correction of dystrophic scoliosis in 31 patients with neurofibromatosis Type 1 using the multiple anchor point method

Abstract: OBJECTIVE The objective of this study was to evaluate the clinical efficacy of posterior-only surgical correction of dystrophic scoliosis in patients with neurofibromatosis Type 1 (NF1) using a multiple anchor point method (MAPM). METHODS From 2005 to 2014, 31 patients (mean age 13.5 years old, range 10–22 years old) suffering from dystrophic scoliosis associated with NF1 underwent posterior-only surgica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 12 publications
0
41
0
Order By: Relevance
“…The clinical outcome of dystrophic scoliosis patients treated with posterior-only fusion by using hooks and rods demonstrated that the pseudarthrosis rate was high and curve progression was common [17]. Recently, some good results of posterior only fusion surgeries in NF-1 patients with dystrophic scoliosis have been reported [9,10,19]. In this study, we reported our results about the posterior only fusion procedure in NF-1 patients with EOS.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The clinical outcome of dystrophic scoliosis patients treated with posterior-only fusion by using hooks and rods demonstrated that the pseudarthrosis rate was high and curve progression was common [17]. Recently, some good results of posterior only fusion surgeries in NF-1 patients with dystrophic scoliosis have been reported [9,10,19]. In this study, we reported our results about the posterior only fusion procedure in NF-1 patients with EOS.…”
Section: Discussionmentioning
confidence: 88%
“…. Recently, the posterior only instrument fusion was reported to be used to treat dystrophic scoliosis in NF-1 patients because challenges for the anterior approach caused by the extensive plexiform tumors could be avoided by using posterior approach and a good short-term result from posterior approach has been reported [9,10]. In Li and his colleagues' study, the posterior only approach demonstrated a good short-term result to treat early-onset scoliosis (EOS) in a group of NF-1 patients with an average age of 13 (the youngest patient was 8 years old), but the number of included patients were not addressed [10].…”
Section: Introductionmentioning
confidence: 99%
“…18,20 In this study, scoliotic curves up to 90 • with flexibility index up to 25% and kyphosis up to 90 • were corrected posteriorly only. Li et al 20 and Deng et al 8 reported similar good results using posterioronly surgery. We think that posterior-only surgery may not be sufficient in dystrophic NF-1 scoliosis curves in the presence of small scalloped deficient apical vertebral bodies that cannot share load and that lead to insufficient apical screw density less than 30%.…”
Section: Used 90mentioning
confidence: 78%
“…The mean follow-up period was 5.15±1.78 years (range, [3][4][5][6][7][8]. The mean operative time was 195±20.12 minutes (range, 160-240) and the mean amount of blood loss was 895.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation